2011
DOI: 10.3844/jssp.2011.152.157
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Public Health Awareness among the Elderly in an Industrially Developing Country

Abstract: Problem statement:The elderly in Industrially Developing Countries (IDC) may encounter problems regarding health. This research is to determine the common diseases or ailments experienced by adults over the age of 40. Approach: A sample of 150 respondents was taken from three states in Malaysia, an IDC. Demographic profiles such as age, gender and race were obtained and questions regarding attentiveness and awareness of health were asked. Four hypotheses were tested. Multiple regression analysis was employed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…These particularities of the participants to Health-Expo campaigns were observed at other similar events organized in several cities of Romania [13,27]. These disproportionalities are very likely a result of self-selection and might be attributed to a heightened interest of women and the elderly toward their health status [28][29][30]. Supposedly, other factors specific to the elderly, such as the availability of free time and a stronger need for socialization might explain their overrepresentation in the studied sample.…”
Section: Discussionsupporting
confidence: 58%
“…These particularities of the participants to Health-Expo campaigns were observed at other similar events organized in several cities of Romania [13,27]. These disproportionalities are very likely a result of self-selection and might be attributed to a heightened interest of women and the elderly toward their health status [28][29][30]. Supposedly, other factors specific to the elderly, such as the availability of free time and a stronger need for socialization might explain their overrepresentation in the studied sample.…”
Section: Discussionsupporting
confidence: 58%
“…To our knowledge, only two studies on elderly smoking were reported for the past 10 years. However, those studies on investigated the smoking prevalence, knowledge and attitude of the elderly toward smoking [ 10 , 19 ], but factors associated with smoking have not been given due attention. Since the factors of smoking among elderly had been reported to be varied from the general population in terms of smoking duration, health status, resistance to quit smoking, awareness on the potential harm of smoking and overestimation on the benefit of smoking [ 20 , 21 ] as well as limited knowledge pertaining to elderly smoking in Malaysia, it is therefore timely to address these existing gaps in knowledge.…”
Section: Introductionmentioning
confidence: 99%